Malay Reading Chart: reading speed testing instrument / Noor Halilah Buari and Ai-Hong Chen - Buari, Noor Halilah; Ai-Hong, Chen (Research Innovation Business Unit, 2014)
Reading chart is one of the important instruments for near reading performance testing in optometric measurement. Various standardized English reading charts are available in the market. However, it is beneficial to have a reading chart in the Malay language to be used among Malay native speakers. Two sets of Malay reading chart were developed in the form of related words and unrelated words namely Malay related words reading chart (MrwRC) and Malay unrelated words reading chart (MuwRC). Purpose: The aims of this testing were to compare the reading speed between MrwRC with the MNRead acuity chart (MNRead) and MuwRC with Bailey-Lovie (BL) reading chart among young adults. Reading chart development: Each MrwRC and MuwRC comprised of two charts. Both charts comprised of fourteen print sizes ranging from 1.3 LogMAR to 0.0 LogMAR, which was equivalent from 8M to 0.4M in 0.1LogMAR steps. Each print size was controlled and had a maximum of 6 words and 12 syllables. The sentence of MrwRC was extracted from Malay textbook of grade 3 to 6 used by primary school of Malaysia Ministry of Education (MMOE). Related words were used to make reading performance evaluation more practical and relevant as in real reading. Whereby the MuwRC was constructed after randomly selected the list of words from Daftar Kata Bahasa Melayu Sekolah Kebangsaan also from MMOE. The unrelated word was made to avoid any contextual cue of the meaning and reading will be solely depends on vision. Font typeface used was Arial. The chart was printed on matte surface white paper to avoid reflection with 100% contrast. Testing protocols: Thirtyone normally sighted young adults were recruited. The participants were asked to read four charts, which were MrwRC1, MrwRC2, MuwRC1, MuwRC2, MNread and BL reading chart aloud and as fast as they can at random sequence. Reading distance was 40cm. Time taken to completed read the each chart was recorded and any error made was noted. Reading speed was quantified as correct words per minute (wpm). Outcomes: Reading speed of MrwRC1 and MrwRC2 were compared between MNRead. The Reading speed of MrwRC1 was not significantly different between MNRead (t(68) = -0.55, p = 0.21). No significant different was also found between reading speed of MrwRC2 and MNRead (t(68) = -0.98, p = 0.33). The reading speed of MuwRC1 (t(60) = 9.11, p = 0.41) and MuwRc2 (t(60) = 7.21, p = 0.30) were compared with BL reading chart and was found no significant different. No significant different were showed in reading speed between MrwRC1 and MrwRC2 (t(68) = 0.27, p = 0.65) and MuwRc1 and MuwRC2 (t(60) = 2.02, p = 0.918). Conclusions: The MrwRC and MuwRC that were developed in short sentences Malay language was comparable with English standardized reading chart i.e MNRead and BL reading chart and proven can be used for reading speed testing among young adults. Both MrwRC (chart 1 and chart 2) and MuwRC (chart 1 and chart 2) can be used interchangeably. The chart can be proposed to vision practitioners as an instrument for near visual acuity testing and reading evaluation in vision rehabilitation among Malay native speakers.